Content Validity and Construct Validity Technical Guidelines for Project Based Learning Based on Chemical Literacy on Reaction Rate Materials - Desi Ratna Sari; Eka Yusmaita (Universitas Negeri Padang, 2022)
This study aims to produce a technical guide for project-based learning based on chemical literacy on the reaction rate material in terms of content validation and construct validation through validation results by experts. This type of research is educational design research using the plomp model. The validity test was carried out by five validators including four chemistry lecturers at the State University of Padang and one chemistry teacher at a senior high school in Padang and analyzed using Aiken's V. The results of the analysis of content validity were 0.82 and construct validity was 0.84. Based on the results of the content and construct validity assessments obtained, the guidelines made can be categorized as valid.